GLYPHOSATE DETERMINATION IN NATURAL WATERS BY FLUORESCENCE SPECTROSCOPY AND SECOND-ORDER MULTIVARIATE CALIBRATION - Manuel Bravo; Veronica Escobar; Sonnia Parra V.; Luis F. Aguilar (Journal of the Chilean Chemical Society, 2025)
In this work, 9-Fluorenylmethoxycarbonyl chloride (FMOC-Cl) and 4-chloro-7-nitrobenzofurazane (NBD-Cl) were evaluated for glyphosate (Gly) determination by fluorescence and second-order multivariate calibration. Additionally, the analytical performance of the UPLS-RBL and MCR-ALS algorithms was compared based on figures of merit and prediction errors. The best results were obtained using NBD-Cl and UPLS-RBL, with a limit of detection (LOD) of 0.3-4.4 µg L-1 and a prediction error (REP) of less than 2%. The FMOC-Cl showed similar figures of merit but inadequate fit in the presence of unexpected interferences. The proposed method was applied to analyze fortified well water, lagoon water, river water, and tap water. Because the matrix effect was significant, the analysis was performed with calibration in the matrix, yielding similar figures of merit and prediction errors to those of the validation set. These results evidenced the analytical potential of the proposed method for monitoring glyphosate in the hydrological cycle.